The effect of Dowex 50 x 4 on the stability of imidazolepyruvic acid - Thamavit, Chirasarit
Imidazolepurivic acid is the alpha-keto analog of histidine. It has been obtained from the urinary metabolite of D-histidine from rats. It is the only compound known to be able to promote slow to moderate growth in the complete absence of histidine.